Teknologi Budidaya Bumina Menggunakan Aliran Air Sistem Rakit - Ayu Agustiani Eka Putri; Bunga Sri Rahma; Lola Anggraini; Ma’rifatul Azizah; Mutia Raidah Asyarifah; Mirna Fitrani (Seminar Nasional Lahan Suboptimal, 2021)
Putri AAE, Rahma BS, Anggraini L, Azizah M, Asyarifah MR, Fitrani M. 2021. Bumina cultivation technology uses a raft system water flow. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 524-529.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Fish farming is one of the livelihoods in Indonesia. The number of people as actors of fish cultivation such as freshwater fish, but is constrained by increasingly limited land, decreasing water quality and quantity, water pollution and the impact of intensification. Therefore, a solution is needed to overcome this problem, namely by making use of a pond called the BUMINA (fruit and fish) pond that uses a raft system water flow. Bumina Pond is a pond that not only produces freshwater fish but is also able to produce certain fruits by utilizing freshwater fish farming on simple land and relatively cheap costs. fruit. The results obtained from Bumina's cultivation are fish, besides that it also produces fruit that increases income.